1980
DOI: 10.1029/ja085ia11p05959
|View full text |Cite
|
Sign up to set email alerts
|

Io and its plasma environment

Abstract: We describe and examine the interaction of Io with its plasma torus and the Jovian magnetic field in the context of several currently popular models. We address three specific matters. First, we discuss features implied by sub-Alfvenic flow which must be common to all models. Next, we examine the magnetic signature observed near Io by the Goddard Space Flight Center Voyager I magnetometer and point out that the preliminary estimate of 5 x 106 A current may be an overestimate. We obtain good fits with alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(66 citation statements)
references
References 32 publications
3
61
0
Order By: Relevance
“…In the Jovian system the AW was first discussed for Io (Goldreich and Lynden-Bell, 1969;Neubauer, 1980;Southwood et al, 1980;Herbert, 1985;Wright and Southwood, 1987;Chust et al, 2005), and the analysis was later expanded to describe the interaction of other Galilean satellites, in particular Europa (Neubauer, 1998(Neubauer, , 1999Khurana and Kivelson, 1999;Volwerk et al, 1999). The properties of the AWs, such as the AW angle θ A , can be useful in determining the local plasma density of the surrounding medium (Neubauer, 1980) if no direct measurements are available.…”
Section: Introductionmentioning
confidence: 99%
“…In the Jovian system the AW was first discussed for Io (Goldreich and Lynden-Bell, 1969;Neubauer, 1980;Southwood et al, 1980;Herbert, 1985;Wright and Southwood, 1987;Chust et al, 2005), and the analysis was later expanded to describe the interaction of other Galilean satellites, in particular Europa (Neubauer, 1998(Neubauer, , 1999Khurana and Kivelson, 1999;Volwerk et al, 1999). The properties of the AWs, such as the AW angle θ A , can be useful in determining the local plasma density of the surrounding medium (Neubauer, 1980) if no direct measurements are available.…”
Section: Introductionmentioning
confidence: 99%
“…Southwood et al (1980) examined data from several Voyager instruments and examined the possible role of an intrinsic magnetic field for Io as a way t o retain a robust enough ionosphere, which could provide enough conductivity for completing the Io-Jupiter current circuit. Neubauer (1980) presented an analytical model of the AlfvGn standing wave current system which connects current through the ionosphere of Io.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the contribution of mass-loading to the plasma currents in the interaction can be equivalently described as a Pedersen conductance (Neubauer 1998a;Hill and Pontius 1998). The Alfvén wing model mentioned above originally was applied to the sub-Alfvénic (M A < 1) interaction between Io and its plasma torus (Goertz 1980;Neubauer 1980;Southwood et al 1980), but it also can be applied to the interactions of the flowing plasma with other moons that have ionospheres and/or a source of neutrals. Even if the flow is superAlfvénic (M A > 1) but sub-magnetosonic (M ms < 1), as for ambient conditions at Titan's orbit, the Alfvén wing model remains a valid description of the interaction.…”
Section: External Sources: Plasma Interaction With Moonsmentioning
confidence: 98%